2016
DOI: 10.3748/wjg.v22.i30.6764
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the old and new concepts in the epithelial-mesenchymal transition of colorectal cancer

Abstract: Epithelial-to-mesenchymal transition (EMT) is defined as the transformation of an epithelial cell into a spindle cell with the loss of membrane E-cadherin expression and the gain of mesenchymal markers positivity. In the field of colorectal cancer (CRC), first data about EMT was published in 1995 and more than 400 papers had been written up to March 2016. Most of them are focused on the molecular pathways and experimentally-proved chemoresistance. In the present article, an update in the field of EMT in CRC ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 68 publications
2
79
0
1
Order By: Relevance
“…Tumor buds have been shown to arise from parts of tumor expressing markers that are associated with epithelial-to-mesenchymal transition (EMT). 13 EMT has been shown to increase invasive and metastatic capabilities of cancer cells, 14 which might explain why patients with high tumor budding have worse outcomes than those who with low tumor budding. Several potential treatments that target EMT in different cancer types are being developed, 15 and could benefit gastric cancer patients with high tumor budding.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor buds have been shown to arise from parts of tumor expressing markers that are associated with epithelial-to-mesenchymal transition (EMT). 13 EMT has been shown to increase invasive and metastatic capabilities of cancer cells, 14 which might explain why patients with high tumor budding have worse outcomes than those who with low tumor budding. Several potential treatments that target EMT in different cancer types are being developed, 15 and could benefit gastric cancer patients with high tumor budding.…”
Section: Discussionmentioning
confidence: 99%
“…β-Catenin and Ecadherin form a complex in the area of cell-cell junction, providing the basis for cell-cell association [67]. Previous studies have shown that ectopic expression of Snail and Ecadherin causes EMT in colorectal cancer [68][69][70]. In CRC, loss of E-cadherin is concomitant with the deregulation of the Wnt/β-catenin signaling pathway and has been characterized as a trait of EMT cells [71].…”
Section: Wnt/β-catenin Signaling and Colorectal Cancer Epithelial-mesmentioning
confidence: 99%
“…Cancer cells undergoing EMT may acquire enhanced proliferation, invasion, and cell migration abilities, and malignant neoplastic cells may acquire resistance to conventional chemoradiotherapy [5]. In CRC, EMT has been shown to stimulate tumor angiogenesis and cancer stem cell traits, which indicates that targeting EMT could be a promising therapeutic strategy for patients with CRC [5].…”
Section: Introductionmentioning
confidence: 99%